The Role of Rakut Si Telu in Karonese society - Sembiring, Milisi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
The researcher applied qualitative research and cultural analysis Ã‚Â to analyze the material and social culture of rakut si telu. The reseacher Ã‚Â participated the Ã‚Â wedding ceremony to explore the practicing Ã‚Â ofÃ‚Â Ã‚Â  rakut si telu. Ã‚Â He has the wedding ceremony texts recorded. Colleting data, classifyingÃ‚Â  the data, and Ã‚Â analyzing data were done scientifically. The result shows the concepts of harmony among Karonese society are the center of Ã‚Â practising Ã‚Â rakut si telu. The role of rakut si telu in Karonese society are important as social standard control. The present of kalimbubu in a wedding party increases prestige of sukut. Anakberu has the role to keep the prestige of sukut. The role of anakberu are responsible to arrange activities in the wedding ceremony. Both groomÃ¢â‚¬â„¢s and brideÃ¢â‚¬â„¢s anakberu serve their each kalimbubu. Both anakberu are as mediators of each kalimbubu in proposing and responding the wedding regularities. Rakut si telu must be preserved Ã‚Â to avoid Ã‚Â negative impact of modern science and to keep Ã‚Â the harmony of the way humanity come to think. Ã‚Â